2010
DOI: 10.3109/1061186x.2010.519031
|View full text |Cite
|
Sign up to set email alerts
|

A thermo-sensitive PLGA-PEG-PLGA hydrogel for sustained release of docetaxel

Abstract: The aim of this study was to investigate the suitability of poly-(d,l-lactic acid-co-glycolic acid) (PLGA)-polyethylene glycol (PEG)-PLGA triblock copolymer as a matrix material for a sustained-release system for docetaxel (DTX). The copolymers were synthesized by ring-opening polymerization reaction and characterized by (1)H-NMR and gel permeation chromatography. The DTX-loaded formulations were prepared, characterized. And the antitumor efficacy and the pharmacokinetics of DTX-loaded copolymer on A-549 lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 36 publications
4
61
2
Order By: Relevance
“…This result is consistent with many previous studies. 23,25) The in vitro release profile was consistent with the Higuchi equation (Q=0.1026t 1/2 +0.0141, r 2 =0.9994). RP was primarily released from the PLGA-PEG-PLGA gel through diffusion.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…This result is consistent with many previous studies. 23,25) The in vitro release profile was consistent with the Higuchi equation (Q=0.1026t 1/2 +0.0141, r 2 =0.9994). RP was primarily released from the PLGA-PEG-PLGA gel through diffusion.…”
Section: Resultsmentioning
confidence: 62%
“…Notably, we observed that the gelation temperature increased at higher RP concentrations, which is a different result from those found in previous reports of drug-loaded PLGA-PEG-PLGA gels. 21,[23][24][25] This discrepancy might be related to the interaction between the drug and the polymer. Some researchers have assumed that the hydrophilic or soluble salts of drug molecules, after absorbing water molecules themselves, can reduce the water activity and access of PEG blocks to the water molecules, thereby facilitating the phase transition at lower temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…After 21 days, the total release of the 1 mg/mL loaded gel was 92.85% while the one of the 4 mg/mL loaded gel was only 76.68%. The increase of viscoelasticity might contribute to the different release characteristics (14). For gelling system, the drug release patterns may be affected by interactions between drug and gel such as hydrophobic or hydrogen bonding interactions (33).…”
Section: In Vitro Release Experimentsmentioning
confidence: 99%
“…Several hydrogels for localized delivery of DTX have been reported such as pluronic F127-based reversal thermal gels (13) and poly-(D,L-lactic acid-co-glycolic acid) (PLGA)-polyethylene glycol (PEG)-PLGA hydrogel (14). Nevertheless, the application of pluronic in drug delivery system is restricted, partly ascribed to its high toxicity and nonbiodegradability (15).…”
Section: Introductionmentioning
confidence: 99%
“…There has been a great deal of interest in the use of hydrogels as chemotherapeutic drug delivery systems for drugs including paclitaxel, doxorubicin, DTX, tamoxifen, and cisplatin. [162][163][164][165][166][167][168][169][170][171] Furthermore, studies have revealed that strategies are required to overcome the disadvantages of chemotherapeutic drugs such as cisplatin, which is usually intravenously administered, whereby 90% becomes linked to hemoproteins and 10% is free to enter into the cells.…”
Section: Hydrogelsmentioning
confidence: 99%